Content of iron and vitamin A in common foods given to children 12–59 months old from North Western Tanzania and Central Uganda - Ekesa, B.; Nabuuma, D.; Kennedy, G. (MDPI, 2019)
Improving infant and young child feeding is an effective intervention to improve child growth. A cross-sectional study followed by observation of selected households was used to establish the most popular foods given to children 12–59 months old in Bukoba and Kiboga districts of Tanzania and Uganda, respectively. Six meals were identified: maize-based porridge, steamed-mashed banana served with beans, banana cooked with beans, banana cooked with groundnut sauce, stiff porridge (Ugali) served with beans and sardines, and cassava cooked with beans. Raw ingredients were transported to Universität für Bodenkultur, Austria, within 48 h and meals prepared following community validated procedures within 24 h by project team members that involved graduate students from East Africa and Europe. High-performance liquid chromatography (HPLC) analysis and microwave digestion followed by flame atomic absorption spectroscopy were used in establishing provitamin A carotenoids and iron content, respectively. Findings indicated no trace of vitamin A or iron in the maize-based porridge, whereas 2.28 mg/100 g ep (edible portion) and 1.18 mg/100 g ep of iron were recorded in stiff-porridge served with beans and sardines and banana cooked with beans, respectively. Banana-based foods had 23 to 43 vitamin A RAE (retinal activity equivalent) µg/100 g ep. With estimated average requirements of iron and vitamin A for children 1–3 years being 5 mg/day and 275 RAE µg/day, respectively, these foods are poor sources of these nutrients in their current form. Thus, there is a need to explore opportunities for modifying preparation methods and incorporating nutritious and diverse ingredients into the foods prepared for infants and young children in Eastern African countries.